2018
DOI: 10.1080/10717544.2018.1466936
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific antibodies (anti-mPEG/anti-HER2) for active tumor targeting of docetaxel (DTX)-loaded mPEGylated nanocarriers to enhance the chemotherapeutic efficacy of HER2-overexpressing tumors

Abstract: Anti-mPEG/anti-human epidermal growth factor receptor 2 (HER2) bispecific antibodies (BsAbs) non-covalently bound to a docetaxel (DTX)-loaded mPEGylated lecithin-stabilized micellar drug delivery system (LsbMDDs) were endowed with active targetability to improve the chemotherapeutic efficacy of DTX. DTX-loaded mPEGylated LsbMDDs formulations were prepared using lecithin/DSPE-PEG(2K or 5K) nanosuspensions to hydrate the thin film, and then they were subjected to ultrasonication. Two BsAbs (anti-mPEG/anti-DNS or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Thus, the BsAb can be modified on diverse mPEG-based materials, such as liposome, Qdot, FeOdot and AuNP 33 and micelle. 38 In addition, by designing a panel of BsAbs, a diverse set of PEG-NPs can be rapidly created to target different biomarkers (e.g., EGFR, 39,40 ICAM-1, 41 etc.) expressed in individual diseases for diagnosis and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the BsAb can be modified on diverse mPEG-based materials, such as liposome, Qdot, FeOdot and AuNP 33 and micelle. 38 In addition, by designing a panel of BsAbs, a diverse set of PEG-NPs can be rapidly created to target different biomarkers (e.g., EGFR, 39,40 ICAM-1, 41 etc.) expressed in individual diseases for diagnosis and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one of the most elegant examples of the strategy can be found in the recent study of Su et al The investigative team targeted the HER2 receptor, known to be overexpressed in breast cancer cells, using PEGylated micelles encapsulating docetaxel. The micelles were further modified by tethering an anti-HER2 antibody to the surface of the micelle via an anti-mPEG linker [68]. This strategy yielded promising results in MCF7 breast cancer cells and demonstrated the power of using antibody targeting as a tool.…”
Section: Surface Modificationsmentioning
confidence: 99%
“…For instance, antibody drug conjugates are being utilized in both preclinical studies as well as early and late stage clinical trials. These studies have shown increased ability to target diseased cells, and increased antitumor potency [140][141][142][143]. Peptide and aptamer based delivery systems have also shown efficacy in reducing offtarget effects and increasing drug delivery to the tumor [144][145][146].…”
Section: Improving Active Targetingmentioning
confidence: 99%